Effects of shot sleeve filling in HPDC machine. Issue 6 (4th November 2019) - Choukri, Korti Mohammed; Nabil, Korti Abdel Illah; Said, Abboudi
Abstract : Purpose: High-pressure die casting is one of the manufacturing techniques used for the rational mass production of metal parts. Due to the high velocity of the molten metal during the injection phase, the die casting of aluminum is so complex and it is almost impossible to calculate these exact performances. Numerical simulation is an effective way to optimize the injection phase and minimize air entrapment that causes porosity defects in the metal. Generally, the filling phase of the molten metal in the shot sleeve is neglected in most scientific work. This phase is followed by a rest period to allow the escape of the resident air bubbles (gravity effect). The paper aims to discuss these issue. Design/methodology/approach: It is relatively clear that the model described poses a great challenge for numerical implementation, especially for 3D geometries. The governing transport equations are solved numerically using the commercial CFD solver Fluent and the equations are discretized using a pressure-based finite volume method. The coupling pressure–velocity was solved by the PISO algorithm. The PISO algorithm takes relatively more CPU time per solver iteration, but it significantly decreases the number of iterations required for the convergence of the transient flow problems. Laminar flow inside air and molten metal was assumed. In order to describe the behavior of the molten metal, a VOF model has been activated. The model makes it possible to account for the moving boundary due to the variation of the shot sleeve volume caused by the plunger displacement. The scheme used in the discretization of momentum equation was the first-order upwind scheme, and the scheme used for the pressure was the PRESTO. The profile of the plunger velocity, boundary conditions change with time and the physical properties change with liquid fraction were used by implementation of a user-defined function. For the discretization of the domain, an unstructured mesh with triangular elements is used. After conducting mesh sensitivity study, a mesh having 53, 813 triangular elements has been chosen for the present study. The convergence criterion was set equal to 10–4 for all parameters. Findings: The results show that the rest and global filling times increase by 2.5 and 8.57 percent with decreasing the pouring velocity by 10 percent. In addition, the rest and global filling times decrease by 5.77 and 8.12 percent with increasing the pouring velocity by 10 percent. Originality/value: After the filling phase, it is necessary to offer a rest period before the injection phase. However, the rest and global filling times increase by 2.5 and 8.57 percent with decreasing the pouring velocity by 10 percent. In addition, the rest and global filling times decrease by 5.77 and 8.12 percent with increasing the pouring velocity by 10 percent. Increasing the pouring velocity by 10 percent leads increasing of the molten metal velocity in the shot sleeve and requires a delay of time of the beginning of the faster plunger movement by 7–10.5 percent. On the other hand, Figure 12 shows that increasing the pouring velocity requires increasing of the plunger velocity during the injection phase, thus increasing the pouring velocity. In order to overcome this problem, it is necessary to reduce the injection velocity and prolong the period of the slower plunger movement.